Four-alarm homicide - Kelly, Diane (Kelly, Diane. House-flipper mystery, 2024)
"Carpenter Whitney Whitaker and her cousin Buck are hot for a historical property that has just come on the market -- a fire station in Nashville's Germantown neighborhood that was built nearly a century ago. The cousins have just begun the interior demolition work at the fire station when Joanna Hartzell, who lives in a townhouse around the corner, comes by with a plea for help. Joanna owns the right half of her building, which she proudly maintains in perfect condition, while the left side falls into disrepair: the seven adult children who inherited it years ago refuse to lift a finger on repairs. Never one to turn down a challenge, Whitney and Buck manage to acquire the rundown townhouse--though it turns out Joanna is only one of the many neighbors interested in buying the property once they've worked their magic. Then Joanna shows up at the fire station confused and rambling, then collapses, never to recover. Alarm bells go off for Whitney: she suspects something--and someone--evil could be the real cause. Can she and Collin put the clues together and smoke out a killer?"--Page 4 of cover.